Utilisation of private general practitioners to provide caesarean deliveries in five rural district public hospitals in South Africa: a mixed-methods study. Issue 3 (1st March 2023) - Doherty, Tanya; Solanki, Geetesh; Daviaud, Emmanuelle; Bartmann, Yvandi; Hawkridge, Anthony; Fawcus, Sue
Abstract : Objective: Researching how public–private engagements may promote universal access to safe obstetric care including caesarean delivery is essential. The aim of this research was to document the utilisation of private general practitioners (GPs) contracted to provide caesarean delivery services in five rural district hospitals in the Western Cape, the profile and outcomes of caesarean deliveries. We also describe stakeholder experiences of these arrangements in order to inform potential models of public–private contracting for obstetric services. Design: We used a mixed-methods study design to describe rural district hospitals' utilisation of private GP contracting for caesarean deliveries. Between April 2021 and March 2022, we collated routine data from delivery and theatre registers to capture the profile of deliveries and maternal outcomes. We conducted 23 semistructured qualitative interviews with district managers, hospital-employed doctors and private GPs to explore their experiences of the contracting arrangements. Setting: The study was conducted in five rural district hospitals in the Western Cape province, South Africa. Results: The use of private GPs as surgeon or anaesthetist for caesarean deliveries differed widely across the hospitals. Overall, the utilisation of private GPs for anaesthetics was similar (29% of all caesarean deliveries) to the utilisation of private GPs as surgeons (33% of all caesarean deliveries). The proportion of caesarean deliveries undertaken by private GPs as the primary surgeon was inversely related to size of hospital and mean monthly deliveries. Adverse outcomes following a caesarean delivery were rare. Qualitative data provided insights into contributions made by private GPs and the contracting models, which did not incentivise overservicing. Conclusion: The findings of this study suggest that private GPs can play an important role in filling gaps and expanding quality care in rural public facilities that have insufficient obstetric skills and expertise. Different approaches to enable access to safe caesarean delivery are needed for different contexts, and contracting with experienced private GP's is one resource for rural district hospitals to consider.